The geography of industry 4.0 in a post-transition country: Comparing firms across Polish regions - Götz, Marta; Jankowska , Barbara; Olejnik , Iwona (European Spatial Research and Policy, 2024)
The ubiquitous nature of the technologies of Industry 4.0 (I4.0) might seemingly make geographic location not matter, leaving regional aspects unimportant. This is due to the common assumption that I4.0 technologies and solutions are agnostic about regional equipment and that their peculiarities are space neutral. In this paper, we conduct a comparative analysis of the regional aspects of the fourth industrial revolution in Poland. The results of our comparative study indicate that the highest degree of saturation in new technologies of I.40 (RDM) is in these regions which are successful in representing high / medium-high technology industries – successfully selling advanced products in high and medium-high technology sectors and are locations of firms that care for their staff and train employees, invest in HR development.